Behavioral determinants for COVID-19 vaccine acceptance among students, faculty, and staff at a rural public university. Issue 1 (31st December 2022) - Bauler, Sarah; Hege, Adam; Davis, Tom; Schluth, Emilee; Pruitt, Caroline; Moreno, Victoria; Verhaeghe, Monica; Bouldin, Erin D.
ABSTRACT: Background: Vaccine hesitancy for COVID-19 is a major obstacle to achieving high vaccine coverage. Low vaccine confidence among college students is one factor fueling the COVID-19 pandemic in the U.S. Objective: The purpose of this study was to evaluate COVID-19 vaccine hesitancy and barriers to vaccine uptake among students, faculty, and staff at a rural public university. Method: We used the Barrier Analysis (BA) mixed-methods approach, which explores determinants of the desired behavior using the Health Belief Model and Theory of Reasoned Action. We developed a BA questionnaire and distributed it through Qualtrics to 4, 600 randomly selected students ( n = 4, 000), faculty ( n = 300), and staff ( n = 300) from March 11 to April 1, 2021. We defined Acceptors as those who were willing to be vaccinated and Non-acceptors as those who were not. Results: Our analysis found that among Non-acceptors, perceived social norms, perceived negative consequences, and trust had the highest association with COVID-19 vaccine hesitancy among students, faculty, and staff. Conclusion: These findings illustrate the need to develop effective behavior change strategies for COVID-19 vaccines uptake that identify sources of trusted information among vaccine-hesitant college students, faculty, and staff, while leveraging enablers to increase COVID-19 vaccination coverage on university campuses.